Productivity and Nutrient Quality of Some Sorghum Mutant Lines at Different Cutting Ages - Rizki Eka Puteri; Panca Dewi Manu Hara Karti; Luki Abdullah; . Supriyanto (Media Peternakan, 2015)
The objective of the study was to explore the appropriate cutting age to produce optimal biomass and good nutrient quality from sorghum mutant lines BMR i.e., PATIR 3.5 M7, PATIR 3.6 M7, and PATIR 3.7 M7, also SAMURAI I (M17). A completely randomized in Split Plot design with 2 factors and 3 replicates was used. The first factor was the type of sorghum (SAMURAI I M17, PATIR 3.5, PATIR 3.6, PATIR 3.7) as the main plot and the second factor was the cutting age (85, 95, 105) as a subplot. Parameters observed were the production of stems, leaves, grains, total biomass production, ash, crude fat, crude fiber, crude protein, NFE, TDN, percentage of DMD, OMD and N-NH3. Data were analyzed by using ANOVA followed by DMRT (Duncan Multiple Range Test). The results showed that there were highly significant interactions (P<0.01) between cutting age and type of sorghum in production of stems, leaves, grains, total biomass production, value of TDN, DMD, OMD, and N-NH3. Increasing cutting age significantly increased the percentage of ash content, crude protein and crude fat. The sorghum type significantly affected crude fat content nonBMR sorghum variety of SAMURAI I (M17) and achieved optimal biomass production and nutrient content at cutting age of 85 d similar to BMR sorghum mutant lines PATIR 3.6 and PATIR 3.5, whereas BMR sorghum mutant lines of PATIR 3.7 achieved optimum production at the age of 95 d of cutting. All types of sorghum varieties was not recommended to be harvested at 105 d. Biomass production increased with the increasing of cutting age, but the nutrient content decreased.Key words: cutting age, mutant, sorghum